2017
DOI: 10.1038/s41467-017-02350-1
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NHEJ repair by type II-A CRISPR-Cas systems in bacteria

Abstract: Type II CRISPR-Cas systems introduce double-strand breaks into DNA of invading genetic material and use DNA fragments to acquire novel spacers during adaptation. These breaks can be the substrate of several DNA repair pathways, paving the way for interactions. We report that non-homologous end-joining (NHEJ) and type II-A CRISPR-Cas systems only co-occur once among 5563 fully sequenced prokaryotic genomes. We investigated experimentally the possible molecular interactions using the NHEJ pathway from Bacillus s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
71
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
2
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(74 citation statements)
references
References 56 publications
(76 reference statements)
2
71
0
1
Order By: Relevance
“…Error-prone repair systems contributing to avoid CRISPR self-targeting could be widespread in bacteria. For example, the non-homologous end-joining (NHEJ) pathway is co-present with the CRISPR-Cas system in some bacterial species 40,41 . However, the NHEJ system has no effect on CRISPR immunity when both NHEJ genes and CRISPR-Cas subtype II-A system were co-expressed in a heterogeneous host 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Error-prone repair systems contributing to avoid CRISPR self-targeting could be widespread in bacteria. For example, the non-homologous end-joining (NHEJ) pathway is co-present with the CRISPR-Cas system in some bacterial species 40,41 . However, the NHEJ system has no effect on CRISPR immunity when both NHEJ genes and CRISPR-Cas subtype II-A system were co-expressed in a heterogeneous host 40 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses have shown that bacterial thermophiles 16 and archaea (both mesophilic and thermophilic) frequently have CRISPR sys-17 tems (∼ 90%), whereas less than half of mesophilic bacteria have CRISPR 18 (∼ 40%; [8,9,10,11,12]). Environmental samples have revealed that many 19 uncultured bacterial lineages have few or no representatives with CRISPR sys- 20 tems, and that the apparent lack of CRISPR in these lineages may be linked 21 to an obligately symbiotic lifestyle and/or a highly reduced genome [13]. Nev- 22 ertheless, no systematic exploration of the ecological conditions that favor the 23 evolution and maintenance of CRISPR immunity has been made.…”
Section: Introductionmentioning
confidence: 99%
“…37 [19,20]). More recently it has been shown that at least one CRISPR-associated 38 (Cas) protein can suppress non-homologous end-joining (NHEJ) DNA repair, 39 which may lead to selection against having CRISPR in some taxa [21]. In or- 40 der to determine the relative importances of these different mechanisms, we 41 must first identify the habitats and microbial lifestyles associated with CRISPR 42 immunity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations